IMPLEMENTASI KEBIJAKAN IZIN PENYELENGGARAAN REKLAME DI KOTA PALU - Djabier, Yan Suprandy (Katalogis, 2015)
The purpose of this research is to understand the compliance of Mayoral regulation objectives on the implementation of the billboard through the implementation process. This study was conducted by using qualitative methodology rules as the basis. The concept used in this study comes from the implementation of Van Meter and Van Horn, the basic sizes and policy objectives, policy resources, communication among organizations and implementation activities, characteristic of the implementing agencies, economic environment, social and politic, tendency of the implementers. The results of this research show that basically, the six indicators have been quite good, but the communication among the institutions needs to be improved in order that the coordination of the five agencies that implement the policy can work well. Besides, Human Resources are also not maximal in implementing the policy due to lack of personnel that making it difficult to maximize the Mayoral regulation.